1973
DOI: 10.1088/0022-3727/6/10/308
|View full text |Cite
|
Sign up to set email alerts
|

Electron swarm parameters in nitrogen

Abstract: Measurements have been made, using recently developed experimental and theoretical techniques, of: the ratio of radial diffusion coefficient to mobility, Dr/μexp; the amplification coefficient, (λL-uL)/p; and Townsend's ionization coefficient, αT/p: for electron swarms in nitrogen for 10 less-than-or-eq, slant E/p less-than-or-eq, slant 450 V cm−1 Torr−1 at 0 °C. The results have been used for the estimation of electron energy distribution and of the mean energy for 30 less-than-or-eq, slant E/p less-than-or-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 15 publications
5
2
0
Order By: Relevance
“…For E/N higher than 200 Td the results of this work, presented in figure 2, are in very good agreement with those by Fletcher and Reid [30] in the E/N overlap. The present results agree excellently with those of Kontoleon et al [44] for E/N 750 Td except for E/N = 500 Td. Above 750 Td the points from work [44] lie lower than ours but the points of Al-Amin et al [43] are situated higher.…”
Section: Characteristic Energy (D/µ) and D L /µ Parametersupporting
confidence: 93%
See 2 more Smart Citations
“…For E/N higher than 200 Td the results of this work, presented in figure 2, are in very good agreement with those by Fletcher and Reid [30] in the E/N overlap. The present results agree excellently with those of Kontoleon et al [44] for E/N 750 Td except for E/N = 500 Td. Above 750 Td the points from work [44] lie lower than ours but the points of Al-Amin et al [43] are situated higher.…”
Section: Characteristic Energy (D/µ) and D L /µ Parametersupporting
confidence: 93%
“…The present results agree excellently with those of Kontoleon et al [44] for E/N 750 Td except for E/N = 500 Td. Above 750 Td the points from work [44] lie lower than ours but the points of Al-Amin et al [43] are situated higher. For 848 Td the difference related to the results of work [43] equals about 18%.…”
Section: Characteristic Energy (D/µ) and D L /µ Parametersupporting
confidence: 93%
See 1 more Smart Citation
“…The results for hydrogen are presented in figures 1 and 2. Below 100Td there is good agreement with the results of Blevin et al (1978a), obtained from current ratio measurements, and Kontoleon et al (1972). For E / N > 100 Td the present data points are a few per cent higher than those quoted above.…”
Section: Related Contentsupporting
confidence: 92%
“…The disagreement between the scaling factors was attributed primarily to the inadequacy of the approximations in the transport code used in the earlier work. Land had attempted to compensate for errors introduced by these approximations by applying corrections that were based on the work of Kontoleon et al (1973). However, Haddad and Milloy showed that corrections became necessary at values of the reduced electric field strength E/N (N is the gas number density) where the transport coefficients were strongly influenced by scattering in the resonance region but where Land had assumed the corrections to be still negligible.…”
Section: Introductionmentioning
confidence: 99%